2018
DOI: 10.25186/cs.v13i2.1422
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of resistance response of Coffea canephora genotypes to Meloiddogyne incognita (Est I2) root-knot nematode

Abstract: ABSTRACT:Meloidogynose is prominent among the factors that limit yield in C. canephora in the western Amazon, Brazil. It is caused by species of "root-knot nematode"; the most important and aggressive of these species for coffee is M. incognita. The aim of this study was to assist the selection of resistant genotypes by characterizing the reaction of 32 C. canephora clones to M. incognita (Est I2). These genotypes are selected plants from the Germplasm Bank of Embrapa Rondônia of the botanical varieties Conilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…As expected, the treatments used as resistant and susceptible controls showed significant differences in the resistance traits means ( Table 2). The reproduction factor of 0.37 of the Apoatã-2258 and BRS2299 treatments indicates that these clones, also classified as resistant by Santos et al, (2018a), showed resistance to M. incognita. Such results confirm the resistance of the Apoatã cultivar which has been used as an alternative in control of root-knot nematodes.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As expected, the treatments used as resistant and susceptible controls showed significant differences in the resistance traits means ( Table 2). The reproduction factor of 0.37 of the Apoatã-2258 and BRS2299 treatments indicates that these clones, also classified as resistant by Santos et al, (2018a), showed resistance to M. incognita. Such results confirm the resistance of the Apoatã cultivar which has been used as an alternative in control of root-knot nematodes.…”
Section: Resultsmentioning
confidence: 98%
“…Plant selection of C. canephora genotypes with resistance to root knot nematodes may be considered in the development of new resistant cultivars (Lima et al, 2015;Fatobene et al, 2018). Of the 32 genotypes of C. canephora evaluated by Santos et al (2018a), it was observed that nine showed higher susceptibility to M. incognita. In a study of 73 wild Coffea spp, plants were identified 18 genotypes of C. canephora resistant to Meloidogyne spp.…”
Section: Introductionmentioning
confidence: 99%
“…classification and nematode resistance. The full-sib clones G10-P8 and G13-P8 of high field yield, also differentiated by their high sieve classification, rust resistance, and uniformity of maturation (SANTOS et al, 2017, SANTOS et al, 2018. In 2019, the clones G10-P8, G13-P8, G14-P4, G16-P7, and G20-P7 were registered in the Ministry of Agriculture and recommended for planting in Western Amazon regions (MAPA/RNC, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Less aggressive and of difficult diagnosis, Meloidogyne exigua is the most widespread species that causes damage to Coffea arabica plants. The species Meloidogyne incognita -EI2 has occurred most in C. canephora cultivation in the state of Rondônia (Santos et al 2018). AL Teixeira et al…”
Section: Responses To Biotic Stressesmentioning
confidence: 99%
“…The resistance response to nematodes was evaluated based on tests conducted in a greenhouse in Porto Velho and Ji-Paraná, RO. Clones considered susceptible through observation showed root knots, eggs, and juveniles of the nematode in the roots exceeding the established standards (Santos et al 2018). When choosing clones for planting, care should be taken when using clones considered to be very susceptible in areas whose history indicates high nematode infestation (Table 4).…”
Section: Responses To Biotic Stressesmentioning
confidence: 99%